2010
DOI: 10.1186/1756-6614-3-10
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of tumor markers doubling time in medullary thyroid carcinoma - preliminary report

Abstract: IntroductionCalcitonin (Ct) and carcinoembrional antigen (CEA) are widely used as tumor markers for the post-operative follow-up of patients with medullary thyroid carcinoma (MTC).In patients with elevated serum Ct and CEA their dynamics can be described by calculating the doubling time (DT) - the time, they need to double the serum concentration. Previous reports concluded that the Ct and CEA DT have prognostic value in MTC patients.Patients and methodsWe retrospectively analyzed data of 70 MTC patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…In agreement with this finding is the The Kaplan-Meier curve of survival in patients with normal and abnormal levels of Ca 19.9. A rapid increase of the Ct and CEA Dt is considered a strong prognostic indicator for MTC recurrence and death, as demonstrated in several studies and metanalyses (16,17,18). This study showed that in our group of advanced MTC, not only the Ct Dt but also abnormal serum levels of Ca 19.9 were prognostic factors of death.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In agreement with this finding is the The Kaplan-Meier curve of survival in patients with normal and abnormal levels of Ca 19.9. A rapid increase of the Ct and CEA Dt is considered a strong prognostic indicator for MTC recurrence and death, as demonstrated in several studies and metanalyses (16,17,18). This study showed that in our group of advanced MTC, not only the Ct Dt but also abnormal serum levels of Ca 19.9 were prognostic factors of death.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, the doubling time (Dt) of both Ct (Ct Dt) and CEA is a strong prognostic indicator for MTC recurrence and death (15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise in DTC, TNM classification allows a better prediction of cancer-related death than the risk of MTC relapse. Moreover, multiple studies, recently published demonstrated a role of calcitonin and carcinoembryonic antigen (CEA) doubling time as an important prognostic factor (Gawlik et al 2010, Wells et al 2015. Therefore, changes in our approach to risk stratification in MTC seem to be necessary, although they have not been recommended yet by the newest MTC ATA GL published in 2015 (Wells et al 2015).…”
Section: Dynamic Risk Stratification In Mtcmentioning
confidence: 99%
“…Besides calcitonin doubling time (9,10,11,12), TNM stage is the most important prognostic factor with 10-year survival rates for stages I, II, III, and IV of 100, 93, 71, and 21% respectively (13).…”
Section: Introductionmentioning
confidence: 99%